Implementasi Manajemen Risiko dalam Penanganan Batu Pack di Pit X PT Bukit Asam Tbk - Muhammad Novaldi Zuhri; Eddy Ibrahim; Taufik Toha (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research identifies and analyzes the implementation of risk management related to the handling of silicified coal in Pit X of PT Bukit Asam Tbk, Tanjung Enim Mining Unit. Through risk management analysis, this study identifies risks that have the potential to cause equipment damage and reduce productivity. The research combines quantitative and qualitative research methods. Primary data was obtained through direct field observation, such as interview questionnaires to identify risks in the stone pack handling process. Secondary data was obtained from literature and company reports. The research stages include preparation, literature study, data collection, data processing and analysis, and research flowcharts. Probability impact matrix analysis and risk index, as well as proposals for risk management control of separating silicified coal from coal. The results show that stone pack clogging is a significant problem that needs to be addressed seriously. This study proposes several risk control strategies to minimize the negative impacts of stone pack clogging, such as improving mining processes, enhancing stone pack separation systems, and training to improve operator skills and awareness. After analyzing the implementation of the risk management system, it is expected to minimize the losses caused by silicified coal on mechanical equipment and other losses in coal mining activities in Pit X Banko, PT Bukit Asam Tbk.